A escrita do aluno surdo e a sequência didática: Uma análise a partir do trabalho com o gênero dissertação escolar - MACEDO, Jaqueline de Sousa (2023)
The work is a research whose main bjective is to analyze how the retextualization of multimodal texts helps in the production of texts written in Portuguese by deaf students. In this bias, the following problem develops: which retextualization strategy(s) are more effective for the production of texts in Portuguese by deaf students? Thus, from the application of didactic sequence of the school dissertation genre to students in the 2nd year of High School through the use of multimodal texts as motivating texts, we intend to understand how retextualization helps in this process of Portuguese writing by the deaf; identifying its advantages in the use of multimodal texts as a didactic tool for an improvement in the textual production of the deaf student. Anchored in Bronckart's socio-discursive interactionism (ISD), the methodology adopted for this study is action research, through the use of didactic interventions allied to the ISD with Bronckart (2007) and of descriptive-exploratory character by use the work of rewriting through the use of multimodal texts. To do so, we start from a debate on textual genres as a teaching tool, based on Marcushi (2008) and Dolz & Schneuwly (2010), among others and on multimodality, studies by Ribeiro (2016) and Dionísio (2005). Our work is developed with deaf high school students from a public school. The results seek to prove the hypothesis that rewriting, aided by the use of multimodal texts as motivators, can be an auxiliary element in the organization and development of the deaf person's thinking and, consequently, an improvement in the production of dissertation texts by this person. Also show possible didactic strategies, thus creating conditions that can lead this deaf person to an improvement both in the production of new texts and writing in Portuguese.